Relationship Between Physical Activity and the Risk of Falls in Elderly People With Diabetes Mellitus in the Working Area of the Simpang Tiga Community Health Center, Pekanbaru - Khofifah Aisyah Fitri; Ari Rahmat Aziz; Safri (International Journal of Health Engineering and Technology, 2025)
The aging process is characterized by a decline in physical function, increasing the susceptibility of the elderly to chronic non-communicable diseases, such as diabetes mellitus (DM), and a heightened risk of falls. This study aimed to determine the relationship between physical activity and fall risk among elderly individuals with DM. Employing a quantitative approach with a descriptive correlational design and a cross-sectional method, the research was conducted on a sample of 108 respondents at the Simpang Tiga Community Health Center in Pekanbaru. Data were collected using questionnaires for demographic information, physical activity, and the Morse Fall Scale (MFS), and analyzed using the Chi-square test. The findings revealed that the majority of respondents had poor physical activity (51.9%) and a high risk of falling (51.8%). A significant relationship was found between physical activity and fall risk (p-value=0.001). The conclusion is that while physical activity is a crucial factor in fall prevention, it is not the only one, and comprehensive strategies are needed.